Prokaryotic community composition and distribution in coastal sediments following a Po river flood event (northern Adriatic Sea, Italy). (5th February 2020) - Fazi, Stefano; Baldassarre, Laura; Cassin, Daniele; Quero, Grazia Marina; Pizzetti, Ilaria; Cibic, Tamara; Luna, Gian Marco; Zonta, Roberto; Del Negro, Paola
Abstract: The influence of the freshwater runoff on marine prokaryotes has been largelly studied in the pelagic environment, little is known about the effects on the prokaryotes in coastal sediments. We investigated the distribution of benthic prokaryotes in the northern Adriatic Sea, when an extreme Po River flood event determined high heterogeneity along the estuarine salinity gradient (from mainly freshwater to marine). The microbial diversity was assessed by 16S rRNA gene Illumina sequencing, the quantification of the dominant taxa of Bacteria and Archaea by microscopy techniques (CARD-FISH). Our results showed dominance of Bacteria (eight-fold higher) over Archaea, and highlighted Proteobacteria as the most represented phylum, followed by Bacteroidetes . Prokaryotic abundance, quantified by DAPI staining, was mainly affected by sediment characteristics (Total Organic C and Total N contents, and silt fraction). Abundance reached the highest values in sites directly affected by the plume (range 7.3 × 10 8 - 2.8 × 10 9  cell g −1 ). A considerable difference in prokaryotes composition was observed along the salinity gradient, with an increasing presence of freshwater taxa at stations more influenced by the river discharge. CARD-FISH analyses corroborated these findings, showing higher abundance of beta-Proteobacteria and Planctomycetes at stations closest to the river mouths. Nevertheless, a core microbiome (about 10% of the total OTUs) was present across all the study areas, indicating the ability of this assemblage to survive in rather diverse environmental conditions, differently impacted by the river plume. Our results show that the river plume can affect the diversity and distribution patterns of benthic prokaryotes far into the pro-delta, although further investigations are needed in order to understand how the mixing of bacterial communities of different origin might reflect on ecosystem functioning. Highlights: The river freshwater plume affects the diversity and the distribution of benthic prokaryotes far into the pro-delta. A core microbiome (about 10% of the total OTUs) was present across all the areas differently impacted by the river plume. The comparison of the results by NGS and CARD-FISH contribute to develop microbial indexes for sediment quality assessment.